Multimodal diagnostic approach and surgical management of suspected malignant gallbladder tumor: A case report - Muhammad Arfan; Samuel Sampetoding; Eva Miranda Fitri; Muhammad Lingga Primananda (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Gallbladder cancer is the most common tumor of the biliary tract and is recognized as one of the most aggressive gastrointestinal malignancies with a poor prognosis. Most cases are diagnosed at an advanced stage, which limits therapeutic options. According to data from the International Agency for Research on Cancer through the Global Cancer Observatory (GLOBOCAN) on 2018, gallbladder cancer ranks 22nd in global cancer incidence and 17th among the leading causes of cancer-related mortality worldwide. Purpose: To describe the diagnostic approach and surgical management of a patient with suspected malignant gallbladder tumor. Method: Descriptive analytic research used a case study approach involving a 51-year-old woman presented with a chief complaint of right upper abdominal pain that had persisted for three months prior to hospital admission. Clinical and diagnostic evaluations were performed using abdominal ultrasonography, multislice computed tomography (MSCT), and magnetic resonance imaging with Magnetic Resonance Cholangiopancreatography (MRI-MRCP) to establish the diagnosis and determine tumor staging. Results: Radiological findings revealed a mass in the gallbladder suggestive of a malignant gallbladder tumor with a clinical stage of cT3N1M0. The patient subsequently underwent surgical intervention through an open laparotomy approach consisting of cholecystectomy combined with resection of tumor-invaded tissues or adjacent organs. Postoperatively, the patient’s condition was stable, and further oncological management with chemotherapy was planned as part of a comprehensive treatment strategy. Conclusion: Gallbladder tumor at stage cT3N1M0 represents an aggressive malignancy that is often diagnosed at an advanced stage. A multimodal diagnostic approach and adequate surgical resection are essential in the management of this condition to improve patient survival outcomes.